The hacker movement as a continuation of labour struggle. - Dafermos, George; Söderberg, Johan (Capital & Class)
Examining the way in which capital exploits the volunteer labour of free software developers, this article argues that there is a historical continuity between hackers and labour struggle. The common denominator is their rejection of alienated work practices, which suggests that corporate involvement in the computer underground, far from inhibiting further struggles by hackers, may function as a catalyst for them. Reprinted by permission of the publisher.